Rational design of an ion-imprinted polymer for aqueous methylmercury sorption - Mesa R.L.M. (2020)
Methylmercury (MeHg+) is a mercury species that is very toxic for humans, and its monitoring and sorption from environmental samples of water are a public health concern. In this work, a combination of theory and experiment was used to rationally synthesize an ion-imprinted polymer (IIP) with the aim of the extraction of MeHg+ from samples of water. Interactions among MeHg+ and possible reaction components in the pre-polymerization stage were studied by computational simulation using density functional theory. Accordingly, 2-mercaptobenzimidazole (MBI) and 2-mercaptobenzothiazole (MBT), acrylic acid (AA) and ethanol were predicted as excellent sulfhydryl ligands, a functional monomer and porogenic solvent, respectively. Characterization studies by scanning electron microscopy (SEM) and Brunauer–Emmett–Teller (BET) revealed the obtention of porous materials with specific surface areas of 11 m2 g?1 (IIP–MBI–AA) and 5.3 m2 g?1 (IIP–MBT–AA). Under optimized conditions, the maximum adsorption capacities were 157 µg g?1 (for IIP–MBI–AA) and 457 µg g?1 (for IIP–MBT–AA). The IIP–MBT–AA was selected for further experiments and application, and the selectivity coefficients were MeHg+ /Hg2+ (0.86), MeHg+ /Cd2+ (260), MeHg+ /Pb2+ (288) and MeHg+ /Zn2+ (1510), highlighting the material’s high affinity for MeHg+. The IIP was successfully applied to the sorption of MeHg+ in river and tap water samples at environmentally relevant concentrations. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.